2016
DOI: 10.1108/jsit-06-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of performance expectancy on commercial farmers’ intention to use mobile-based communication technologies for agricultural market information dissemination in Uganda

Abstract: Purpose This paper to examine the relationship between performance expectancy and behavioural intention to use mobile-based communication technologies for agricultural market information dissemination in Uganda. Design/methodology/approach A descriptive field survey method was adopted. A total of 302 commercial farmers and agribusiness traders in Eastern Uganda participated in the study from whom data were collected using self-administered questionnaires. Descriptive statistics, factor analysis, correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 14 publications
4
29
0
1
Order By: Relevance
“…Performance expectancy refers to the belief that the use of technology in certain situations can be beneficial as it improves performance (Venkatesh et al 2012). Studies with UTAUT as the theoretical framework have always shown that there is a statistically significant relationship between expected performance and user acceptance of the technology's behavioral intent (Engotoit, Kituyi, and Moya 2016;S. Raschid Muller and Mary L. Lind 2020).…”
Section: Performance Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Performance expectancy refers to the belief that the use of technology in certain situations can be beneficial as it improves performance (Venkatesh et al 2012). Studies with UTAUT as the theoretical framework have always shown that there is a statistically significant relationship between expected performance and user acceptance of the technology's behavioral intent (Engotoit, Kituyi, and Moya 2016;S. Raschid Muller and Mary L. Lind 2020).…”
Section: Performance Expectancymentioning
confidence: 99%
“…(Šumak, Polančič, and Heričko 2010) stated that performance expectancy directly affects behavioural intentions towards use of Moodle, but this study is biased towards students who have already technical skills for using the tool. (Engotoit et al 2016) investigated the performance expectancy's influence on commercial farmers' intention to use mobile banking communication systems in Uganda. The research interviewed 302 farmers.…”
Section: Performance Expectancymentioning
confidence: 99%
“…Research suggests that social media can strengthen college students’ communication with peers and teachers (Mirabolghasemi et al, 2016; Ellison et al, 2007), as well as, encourage goal-setting, self-monitoring, and self-reflection when learning in digital environments (Dabbagh and Kitsantas, 2012). Performance expectancy has also been identified for significantly influencing behavioral intention to use mobile-based communication technologies (Engotoit et al, 2016), which in turn has been suggested to increase social media adoption rates (Poushter, 2016). Based on related literature, we propose that college students’ performance expectancy may be related to their digital citizenship.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Furthermore, Cole and Fernando (2012) pointed out that mobiles reduce the cost of individual visits, enhance feedback between farmers and extension workers, and overcome lack of extensionists and poor infrastructure. Consequently, assessment of mobile utilization by the farmers and its impact on agriculture has been a key research area over the past decade (Aldosari et al,2017;Car et al, 2012;Dey et al, 2016;Engotoit et al, 2016;Ganesan et al, 2013;Hasan, 2015;Krone et al, 2014; 2016; Okuboyejo and Adejo, 2012;Tadesse and Bahiigwa, 2015;Verma and Sinhab, 2018;Wijeratne and De Silva, 2014;Wyche and Steinfield, 2016).…”
Section: Introductionmentioning
confidence: 99%